Persepsi Masyarakat Muslim Desa Serba Jadi Dusun IV Kecamatan Sunggal Kabupaten Deli Serdang Tentang Komunikasi Kelompok Geng Motor - Aji Gusti Arjaya Aji; Candra Gunawan (Bashirah, 2022)
This study aims to determine how the perception of the Muslim community in Serba Jadi Hamlet IV Village, Sunggal District, Deli Serdang Regency about motorcycle gang group communication. This research was conducted in Serba Jadi Village, Hamlet IV, Sunggal District, Deli Serdang Regency. In this study, researchers used a one-sample quantitative method. The sample of this research is the Muslim community of Serba Jadi Hamlet IV Village, totaling 35 people. The results showed that the Muslim community of Serba Jadi Hamlet IV Village, Sunggal District, Deli Serdang Regency had a bad perception of motorcycle gang group communication, which was at most 65%, this was in accordance with the researcher's hypothesis. It can be seen from the one sample t test that has been carried out, where t count (-6.176) < t table (-1.689) with an error rate of 5%, it can be concluded that Ho is accepted and Ha is rejected. With the acceptance of Ho and the rejection of Ha, it can be stated that most people have a bad perception of motorcycle gang group communication at most 65%.